Journey of Medical Education Department, BCPS: Its Contribution in Developing Skilled Fellows for Effective use of Assessment Tools - Afroze, Samira Rahat; Hasan, Md Mehedi; Jamal, ABM; Begum, Tahmina (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Abstract not available J Bangladesh Coll Phys Surg 2022; 40: 107-109